Supramolecular Structure of 2,4,6-Trinitrophenol - Sun, Yin-Xia; Ren, Zong-Li; Meng, Wei-Sheng (Asian Journal of Chemistry, 2013)
The compound 2,4,6-trinitrophenol with the molecular formula C6H3N3O7, crystallizes with two crystallographically independent but chemically identical molecules in the asymmetric unit. The dihedral angle formed by the two benzene rings is about 67.49º. The crystal structure displays four intramolecular hydrogen bonds between the hydrogen atoms from the phenolic alcohols and the oxygen or nitrogen atoms from the nitro groups. In the crystal structure, the intermolecular O-H···O and C-H···O hydrogen bonding interactions link molecules into infinite three-dimensional supramolecular network structure.